2018
DOI: 10.21608/bvmj.2018.54243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Dietary Supplementation on Economic efficiency of growing Japanese Quails

Abstract: This work was conducted to study the effect of sun dried tomato pomace (SDTP) with or without enzymes supplementation economic efficiency of Japanese quail. A total number of 306 sevendays-old quail chicks were used. The quail chicks were randomly allocated into 6 groups (51 unsexed chicks per group). Group 1 was fed on the basal diet (BD) without enzymes supplementation (control), quail chicks of group 2 were fed on the BD containing AveMix® 02 CS enzyme 0.02g/kg diet. While quail chicks of group 3 were fed B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
4
6
0
Order By: Relevance
“…Concerning TC effect on TR, about 74% from the changes in TR were attributed to the changes in the TC, the increasing in TC by about 1% led to increase TR by about 3.70%. This result was in accordance with Shehata et al (2018) who found a significant effect of TC on TR in different dietary supplemented groups.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning TC effect on TR, about 74% from the changes in TR were attributed to the changes in the TC, the increasing in TC by about 1% led to increase TR by about 3.70%. This result was in accordance with Shehata et al (2018) who found a significant effect of TC on TR in different dietary supplemented groups.…”
Section: Discussionsupporting
confidence: 93%
“…Shehata et al (2018) confirmed that the addition of tomato pomace by 5% without enzymes to quail diets increased final weight of 29.36% as compared to control at 42 days of age. The findings of the present study for body weight and body weight gain were in line with previous researches in broilers (Ali & Al Massad, 2015;Sahin et al, 2016), quails (Shehata et al, 2018) and geese (Al-Janabi, 2015), who found a positive effect on growth performance when tomato and tomato residuals and lycopene used in poultry ration. On the other hand, in broilers, weight gain, feed intake and feed efficiency did not change significantly with the inclusion of 10 and 20 (mg.kg -1 ) of lycopene or 17 (g.kg -1 ) of tomato paste (which was equivalent to 5 ppm of lycopene) in experiment lasted four weeks (Lee et al, 2016).…”
Section: Production Performancesupporting
confidence: 63%
“…As well as, this improvement in growth performance may be due to the positive effect of lycopene on gut physiology in broiler chickens (Sun et al, 2015). Shehata et al (2018) confirmed that the addition of tomato pomace by 5% without enzymes to quail diets increased final weight of 29.36% as compared to control at 42 days of age. The findings of the present study for body weight and body weight gain were in line with previous researches in broilers (Ali & Al Massad, 2015;Sahin et al, 2016), quails (Shehata et al, 2018) and geese (Al-Janabi, 2015), who found a positive effect on growth performance when tomato and tomato residuals and lycopene used in poultry ration.…”
Section: Production Performancementioning
confidence: 59%
“…The economic evaluation was determined by considering feed cost per chicken (USD), total income from the chicken (USD), and growth efficiency according to Gondwe and Wollny (2005). The total return (TR) was calculated according to Shehata et al (2018). The European performance efficiency index (EPEI) was evaluated according to Panda et al (2006).…”
Section: Economic Evaluationmentioning
confidence: 99%